Infections in hospitalized children and young adults with acute leukemia in Morocco1. Issue 6 (28th February 2013) - DePasse, Jacqueline; Caniza, Miguela A.; Quessar, Asmaa; Khattab, Mohammad; Hessissen, Laila; Ribeiro, Raul; Cherkaoui, Siham; Benchekroun, Said; Matthay, Katherine K.
Abstract Background Overall survival from leukemia is less in low and middle‐income countries than in high‐income countries. Our purpose was to describe the incidence, clinical features, and mortality of febrile illness with or without documented infection in children and young adults treated for AML and ALL in two centers in Rabat and Casablanca during 2011. Methods This retrospective cohort study included patients <30 years of age who were newly diagnosed with AML and ALL in 2011 in Casablanca and Rabat. Each patient's chart was evaluated for patient demographics, febrile episodes, chemotherapy regimen, and clinical or microbiological evidence of infection, neutropenia, antibiotics, and mortality. Results One hundred sixty‐six evaluable patients had 228 inpatient febrile episodes. The median number of febrile episodes in AML was three per patient, and for ALL, one per patient. Clinically identified infections mainly included pneumonitis and mucositis. Coagulase negative staphylococcus was the most commonly isolated bacterium, followed by gram‐negative bacteria. Fifty‐three percent of febrile episodes were classified as fever of undetermined origin. Broad‐spectrum antibiotics were routinely used, with the addition of antifungals in 62 episodes and vancomycin in 83 episodes. The rate of deaths per febrile illness was 11.3% (16/141) in patients with AML, and 9.2% (8/87) in patients with ALL. Conclusion The higher rate of infectious deaths in leukemia compared to that reported in high‐income countries, suggests that improvements in infection care and prevention, including consistent access to rapid hospitalization, diagnostics and antibiotics; and standardizing quality of patient care are necessary to improve as well as survival in patients with leukemia in Morocco. Pediatr Blood Cancer 2013; 60: 916–922. © 2013 Wiley Periodicals, Inc.